2018
DOI: 10.1186/s13045-018-0621-5
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB signaling and its relevance to the treatment of mantle cell lymphoma

Abstract: Mantle cell lymphoma is an aggressive subtype of non-Hodgkin B cell lymphoma that is characterized by a poor prognosis determined by Ki67 and Mantle Cell International Prognostic Index scores, but it is becoming increasingly treatable. The majority of patients, especially if young, achieve a progression-free survival of at least 5 years. Mantle cell lymphoma can initially be treated with an anti-CD20 antibody in combination with a chemotherapy backbone, such as VR-CAP (the anti-CD20 monoclonal antibody rituxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 68 publications
2
38
0
1
Order By: Relevance
“…also find that the phosphorylation of Akt could be regulated to promote GBC cell growth, metastasis and epithelial‐mesenchymal transition (EMT) . In additionally, recent evidences indicate the occurrence of Akt hyperactivation can significantly influence its downstream effectors, such as NF‐κB, which mediates cell survival and proliferation . Researchers find that Akt transiently binds to the inhibitor of kappa B kinase (IKKα) and induces IKK activation, which in turn allows NF‐κB to translocate to the nucleus and trigger expression of target genes .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…also find that the phosphorylation of Akt could be regulated to promote GBC cell growth, metastasis and epithelial‐mesenchymal transition (EMT) . In additionally, recent evidences indicate the occurrence of Akt hyperactivation can significantly influence its downstream effectors, such as NF‐κB, which mediates cell survival and proliferation . Researchers find that Akt transiently binds to the inhibitor of kappa B kinase (IKKα) and induces IKK activation, which in turn allows NF‐κB to translocate to the nucleus and trigger expression of target genes .…”
Section: Introductionmentioning
confidence: 99%
“…19 In additionally, recent evidences indicate the occurrence of Akt hyperactivation can significantly influence its downstream effectors, such as NF-κB, which mediates cell survival and proliferation. 20,21 Researchers find that Akt transiently binds to the inhibitor of kappa B kinase (IKKα) and induces IKK activation, which in turn allows NF-κB to translocate to the nucleus and trigger expression of target genes. 22 Furthermore, it is found that inactivation of Akt could prevent the progression of breast cancer by block the NF-κB pathway.…”
mentioning
confidence: 99%
“…For example, in some MCL cases, the inhibition and inactivation of phosphatase and tensin homolog (PTEN) confers constitutive activation of AKT, which may promote chemoresistance (25). The PI3K (phosphatidylinositol 3-kinase)-AKT-mTOR (mammalian target of rapamycin) and NF-В pathways are unusually active in the pathogenesis of MCL (26,27). Furthermore, there is evidence that MCL tumor cells can activate alternative pathways when classical signaling is quenched (17).…”
Section: Interrogating B Cell Signaling Pathwaysmentioning
confidence: 99%
“…IMiDs are widely used in combination with proteasome inhibitors, steroids, and monoclonal antibodies and playing a pivotal role in the treatment of multiple myeloma (MM) [12][13][14][15][16][17][18]. Lenalidomide also showed activities in a number of hematological malignancies, including myelodysplastic syndrome (MDS) with deletion of chromosome 5q (del(5q)) [19][20][21], mantle cell lymphoma (MCL) [22][23][24][25][26][27] and chronic lymphocytic leukemia (CLL) [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%